Deteksi Fraud Financial Statement Menggunakan Model Fraud Pentagon Pada Perusahaan Yang Terdaftar di JII Tahun 2016-2018 - Ahmad Naufal Fadhlurrahman (ITB AAS INDONESIA Surakarta, 2021)
This study aims to analyze the proxies that are considered to be able to detect financial statement fraud with the pentagon fraud model. This model is a development of the fraud triangle and fraud diamond models by adding arrogance elements to complement the previous four existing elements, namely pressure, opportunity, rationalization, and competence. The population used in the study are companies listed on the 2016-2018 Jakarta Islamic Index (JII). Company samples obtained using purposive sampling technique are 14 companies and tested using multiple regression analysis. The results obtained from this study indicate that the stability proxied by changes in total assets and changes in directors as a proxy of the competency element has an influence in predicting financial statement fraud, while the opportunity, rationalization and arrogance elements do not affect financial report fraud. It is hoped that this research can be developed by extending the research years and proxies that represent each element of this model.